Delusions of progress: A case for reconceptualising environmental education - Malcolm Plant (Environmental Association of Southern Africa, 1995)
The great modem project that was bent on using technology to improve the human condition through the control of nature has not worked out as its earlier proponents once promised. By assuming that economic growth and technological progress are ways to a cleaner environment and social equality, humanity has created unprecedented social and environmental problems. The more we exercise power over nature, the less predictable and resilient nature has become. The more wealth we produce, the wider the economic gap between rich and poor. But few would argue that ecological damage is, primarily, the fault of technology: It is first and foremost a crisis of mind which makes it a crisis for those institutions which purport to improve minds. This is a crisis of education ... (Orr, 1994). Broadly responding to the theme of this conference, this paper critically examines the 'crisis of education'. I begin by reflecting on my own limited experience of teaching in Africa, not to claim any legitimacy for speaking on behalf of (South) Africa but in an attempt to unmask my own (past?) naive complicity in the 'crisis of education'. A brief analysis of 'progress' and the dynamics of 'globalisation' serves to illustrate the complexity, uncertainty and change in modem society which necessitate a continual and reflexive testing of new paradigms for environmental education. One such paradigm is a socially critical pedagogy which is inherently interdisciplinary and which is advanced as a transformative learning process promoting teachers' own well-being. I then propose, tentatively, a way of locating this paradigm within a more general theory that draws on recent understanding of the dynamics of complexity and disorder and reveals the world as sensitive, fragile and unpredictable. This is the theory of chaos, a core concept of which is the notion of an 'attractor' that may be used as a metaphor for establishing a new benchmark of confidence for environmental educators to counter the dominant metaphor of progress, the laplacian dream of discovering the deterministic rules that enable us to predict and control the future. The issues raised in this paper are of interest to the author's research and teaching, a distance learning MAin Environmental Education through Action Enquiry at Nottingham Trent Unversity, UK, with Roger Firth. ... the idea of great progress is a delusion,along with the idea that the truth will ultimately be known. (Wittgenstein, 1980) Progress might have been alright once, but it's gone on too long. (Ogden Nash, quoted by Provine, 1988)